Las condiciones del cuidado en familias antioqueñas con un miembro con trastorno afectivo bipolar (2013)
ABSTRACT: This article is a report on the research “Care practices and family burden in families from Antioquia, Colombia, with a member diagnosed with bipolar affective disorder”. Objective: To recognize the context of the care provided to family members diagnosed with such disorder. Method: a qualitative study using the phenomenological and hermeneutic approach was done. Data were collected via in-depth interviews with the 12 families participating in the study, and a genogram was built. Results: two factors explain the increased stress and fatigue observed in family members taking care of a person with a mental condition: the first one is associated with the caregiver, and the second one, with the material and immaterial conditions of the care provided. Conclusions: (1) stress and fatigue are low when individuals willingly choose to take care of the person with a mental condition and thus define themselves as caregivers; (2) the quality and type of the bond established between the diseased person and the caregiver are strong predictors of family stress and fatigue; (3) this condition challenges the identity of the family and that of each one of its members.